Study of Water Desorption Isotherms from Cocoa Beans (Theobroma Cacao L.) of Cameroon - Bidias, J. B; Mouthe Anombogo G. A.; Ndjeumi C. C; Djomdi Djomdi; Tchaya G. B.; Nsouandele J. L (European Scientific Journal, ESJ, 2022)
The aim of this work was the determination of desorption isotherms from cocoa beans at different temperatures (20°C, 30°C, 35°C, 40°C and 45°C), moisture ratio (10% and 90%). Gravimetric method and different temperatures were used to get the experimental moisture ratio at equilibrium. Experimental data were adjusted to mathematical isotherm models frequently used for the hygroscopic representation of agricultural products. Cocoa beans varied from 0 to 13% moisture ratio equilibrium. Obtained results showed that the moisture ratio at equilibrium decreases as temperature increases for the same relative humidity. Statistical parameters, modified the Oswin model, GAB, Iglesias Chirife Hasley and Chungs Pfost modified model better represented hygroscopic balance for cocoa beans than Henderson modified and Harkings Jura models. Desorption isotherm models are important for the determination of desorption energy and drying models. The desorption isotherms of cocoa beans were satisfactorily modeled by modified Oswin, GAB, Iglesias, Chirife, Halsey, and modified Chungs Pfost, which can be used as tools in the prediction and optimization of storage conditions in a wide range of water activities and temperatures.